Industry 4.0 implies lean manufacturing: Research activities in industry 4.0 function as enablers for lean manufacturing - Adam Sanders; Chola Elangeswaran; Jens P. Wulfsberg (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: Lean Manufacturing is widely regarded as a potential methodology to improve productivity and decrease costs in manufacturing organisations. The success of lean manufacturing demands consistent and conscious efforts from the organisation, and has to overcome several hindrances. Industry 4.0 makes a factory smart by applying advanced information and communication systems and future-oriented technologies. This paper analyses the incompletely perceived link between Industry 4.0 and lean manufacturing, and investigates whether Industry 4.0 is capable of implementing lean. Executing Industry 4.0 is a cost-intensive operation, and is met with reluctance from several manufacturers. This research also provides an important insight into manufacturers' dilemma as to whether they can commit into Industry 4.0, considering the investment required and unperceived benefits. Design/methodology/approach: Lean manufacturing is first defined and different dimensions of lean are presented. Then Industry 4.0 is defined followed by representing its current status in Germany. The barriers for implementation of lean are analysed from the perspective of integration of resources. Literatures associated with Industry 4.0 are studied and suitable solution principles are identified to solve the abovementioned barriers of implementing lean. Findings: It is identified that researches and publications in the field of Industry 4.0 held answers to overcome the barriers of implementation of lean manufacturing. These potential solution principles prove the hypothesis that Industry 4.0 is indeed capable of implementing lean. It uncovers the fact that committing into Industry 4.0 makes a factory lean besides being smart. Originality/value: Individual researches have been done in various technologies allied with Industry 4.0, but the potential to execute lean manufacturing was not completely perceived. This paper bridges the gap between these two realms, and identifies exactly which aspects of Industry 4.0 contribute towards respective dimensions of lean manufacturing.
Keywords: 650; production management; lean manufacturing; industry 4.0; cyber physical systems; internet of things